Ligamentum flavum hematoma: a case report and literature review - Sfreddo,Ericson (2012)
The aim is to present a rare case of ligamentum flavum hematoma in the lumbar region, discuss its physiopathology and treatment and review the literature. A woman aged 68 presented with neurogenic claudication due to degenerative lumbar spondylolisthesis that evolved into a sudden worsening with cauda equina syndrome. The magnetic resonance imagining (MRI) showed signs of degeneration of the lumbar spine, with a narrow spinal canal from L2 to S1, anterolisthesis L4 L5 and an expansive lesion hyperintense on T1-weighted and hypointense on T2-weighted images considered compatible with hematoma in the topography of the yellow ligament in L1-L2. The patient underwent laminectomy and lumbar fixation. Her evolution was good in the postoperative period and at 18 months of follow-up hse walked alone, despite the pain that is controlled with simple medications. Even though rare, it seems that ligamentum flavum hematoma has a relationship with the degeneration and rupture of small vessels associated with micro trauma to the spine. Its physiopathology is not well defined and treatment is similar to other spine compression processes.